Research on the Operating Mechanism of E-Commerce Poverty Alleviation in Agricultural Cooperatives: An Actor Network Theory Perspective - Xu, Na; Xu, Chi; Jin, Yuanbo; Yu, Zhenjie (Frontiers in Psychology, 2022)
E-commerce poverty alleviation has become a new wisdom in China's rural poverty alleviation, but there are a few empirical researches on e-commerce poverty alleviation based on farmer cooperatives. Taking four typical poverty counties in Zhejiang Province as an example, based on the actor network theory (ANT), this paper defines the participants and their obligatory passage point (OPP) from the e-commerce poverty alleviation actor network (EPAAN), combs the roles and interest demands of various stakeholders, and constructs the EPAAN model based on farmer cooperatives according to the translation process. We found that the EPAAN is a heterogeneous network by constantly updating, which consists of human actors with farmer cooperatives as the main body and non-human actors. Moreover, our study illustrates that the formation and operation mechanism of cooperative e-commerce poverty alleviation network alliance under the background of targeted poverty alleviation can be well analyzed with the help of actor network theory. This study contributes to provide a feasible Chinese plan for the cause of poverty eradication all over the world, and provides a great reference value for global poverty governance.